Quantification of Salmonella enterica serovar Typhimurium population dynamics in murine infection using a highly diverse barcoded library - Julia A Hotinger; Ian W Campbell; Karthik Hullahalli; Akina Osaki; Matthew K Waldor (eLife)
Murine models are often used to study the pathogenicity and dissemination of the enteric pathogen Salmonella enterica serovar Typhimurium. Here, we quantified S. Typhimurium population dynamics in mice using the STAMPR analytic pipeline and a highly diverse S. Typhimurium barcoded library containing ~55,000 unique strains distinguishable by genomic barcodes by enumerating S. Typhimurium founding populations and deciphering routes of spread in mice. We found that a severe bottleneck allowed only one in a million cells from an oral inoculum to establish a niche in the intestine. Furthermore, we observed compartmentalization of pathogen populations throughout the intestine, with few barcodes shared between intestinal segments and feces. This severe bottleneck widened and compartmentalization was reduced after streptomycin treatment, suggesting the microbiota plays a key role in restricting the pathogen’s colonization and movement within the intestine. Additionally, there was minimal sharing between the intestine and extraintestinal organ populations, indicating dissemination to extraintestinal sites occurs rapidly, before substantial pathogen expansion in the intestine. Bypassing the intestinal bottleneck by inoculating mice via intravenous or intraperitoneal injection revealed that Salmonella re-enters the intestine after establishing niches in extraintestinal sites by at least two distinct pathways. One pathway results in a diverse intestinal population. The other re-seeding pathway is through the bile, where the pathogen is often clonal, leading to clonal intestinal populations and correlates with gallbladder pathology. Together, these findings deepen our understanding of Salmonella population dynamics.